Major contributing factors to the lower level of connection to the existing sewer network in Addis Ababa: the case of the Kality catchment - Ali, Mohammed; Robele, Sirak (Frontiers in Environmental Engineering, 2023)
Many households in Addis Ababa have not been connected to a sewer network, even when it passes by their homes. This study was designed to investigate major factors that have contributed to the lower level of connection to the existing sewer network in the Kality catchment of Addis Ababa. A household survey was conducted via questionnaire to identify the reasons hindering customers from connecting to sewers. The main factors identified were lack of awareness, connection fee, topography, customers’ preference for onsite sanitation over sewers, customers’ unwillingness to reinstate fences or pavements in their compound, and the unreliability of the water utility service. The survey results were analyzed with a binary logistic regression model using SPSS software. Except for topography (p-value 0.792) and connection fee (p-value 0.446), the other four independent variables had significant p values of less than 0.05, which implied a good model. Customers’ preference for onsite sanitations over sewers, followed by the unreliability of the water utility service and customers’ unwillingness to reinstate fences or pavements in their compounds were found to be the factors that most contribute to the lower level of user interest in sewer connection. However, a lack of awareness and information was also crucial in determining the rate of connection to sewers in the Kality catchment of Addis Ababa. The study also revealed that there was a gap in legislation and its enforcement: there was neither a regulator nor regulations for monitoring wastewater management, including mandatory sewer connection in the city.